Penilaian keseimbangan pada siswa dengan gangguan pendengaran - Ekawati, Febriani Fajar; Rahayu, Tri Winarti; Ismaryati, Ismaryati; Satyawan, Budhi; Meli Andani, Abrean (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Balance is the ability to maintain body position when moving or standing still. Therefore, children must have this ability to move correctly. Children with hearing loss have problems in their vestibular system, consequently disturbing their daily activity concerning balance condition. This study aimed to evaluate the balance of students with hearing impairment in Karanganyar, Central Java. The present survey study used the Balance Test to measure 59 (male = 31, female = 28) hearing-impaired students’ balance. Descriptive statistics analysis was used to calculate the mean of all participants and every gender group. The result revealed that the average balance score of all students was 1,136, the highest score was 4, and the lowest was 1. Concerning gender, females performed slightly better than males on the balance test, with scores of 1,143 and 1,129, respectively. Of the 59 students, more than 90% of females and males were categorized as poor, and more than 3% were classified as moderate and very good. The study suggests that the balance score of hearing-impaired students was low.